The notion of Mahdiyyah as conceived by Sheikh ʿUsmān Dan Fodio - Adam, Abba Idris; Ibrahim, Hassan Ahmed (IIUM Press, 2017)
The belief in the expected redeemer or the Mahdī is a well-known concept in the history of Islam. However, the notion has been opened to several interpretations and misinterpretations from various Islamic sects, each asserting that its own version of the Mahdiyyah is authentic and valid. As a result, several Islamic movements were orchestrated under the banner of the Mahdiyyah; prominent among them in Africa are those of Muhammad Ibn Tumart (1080-1130), the patron of the Muwaḥḥidūn State in north Africa, Muḥammad AÍmad ibn ʿAbdullāh (1844-1885), the architect of the Mahdist State in the Sudan (1881-1898) and Sheikh ʿUsmān Dan Fodio (1754-1817), the founder of the Sokoto Caliphate. This article explores the authenticity of the notion of the Mahdiyyah in Islam, which constitutes the basis for the main discourse of the study, namely, the status of the Mahdiyyah as conceived by Sheikh Usman Dan Fodio, and the resultant impact of the Sheikh’s Mahdiyyah on the Sudanese Mahdiyyah.